Differences in quality of care, mortality, suicidal behavior, and readmissions among migrants and Danish-born inpatients with major depressive disorder. Issue 1 (21st October 2022) - Knudsen, Søren Valgreen; Valentin, Jan Brink; Norredam, Marie; Videbech, Poul; Mainz, Jan; Johnsen, Søren Paaske
Abstract: Background: The increasing global migration has made migrants' health a pertinent topic. This article aimed to examine whether migrants were less likely than Danish-born residents to receive guideline recommended care when hospitalized for major depressive disorder (MDD) and potential differences in clinical outcomes, including all-cause mortality, suicidal behavior, and readmissions during 1-year follow-up after first-time admission. Methods: A national cohort study was performed, including all adult MDD inpatients at mental care units in the period 2011–2017. Migrants and two migrant subgroups (non-Western and Western) were compared with Danish-born patients. Quality of care was examined using multivariable Poisson and linear regression models. Clinical outcomes were examined using Cox proportional hazards regression analysis. Results: Migrant-status was associated with a non-significantly lower chance of receiving high-quality care (relative risk [RR] = 0.93, confidence interval [CI] 0.86:1.01) and lower readmission rates for depression (hazard rate ratio [HR] = 0.93, CI 0.86:1.01), and significantly higher all-cause mortality (HR = 1.55, CI 1.19:2.01) and lower all-cause readmission rate (HR = 0.88, CI 0.83:0.94). No clear association was found regarding suicidal behavior. While associations were comparable for migrant subgroups regarding readmission, the associations with low quality of care and of all-cause mortality appeared strongest among Western migrants. Conclusions: Among inpatients with MDD in a universal tax-financed healthcare system, being a migrant was associated with a potential lower quality of in-hospital care and worse clinical outcomes. These results warrant further investigation to clarify the underlying explanation for these inequalities and to develop and test interventions to ensure better quality of care and clinical outcomes for migrant patients.